Divorce and Intergenerational Support: Comparing the Perceptions of Divorced Adults and Their Parents - TIMONEN, VIRPI (My University, 2012)
Many studies have indicated that intergenerational support may be required when people separate from their spouse. However, the difference between the younger and older generation's experience of such intergenerational support at a time of divorce is under-researched. This article examines differences in perceptions of divorced adults and their parents, hereafter referred to as the younger and older generation. The analysis is based on two different sample sets of in-depth interviews conducted in 2008 in Ireland. Findings from the interviews showed that, whereas the older generation believed they provided both emotional and practical support (financial, childcare and housing), the younger generation felt they received and benefited from practical support over and above emotional support. The findings show a striking divergence in perceptions of emotional support between, the two generations. The article contributes to the discussion of the structure and meaning of intergenerational support at a time of divorce and discusses the factors which impact upon the experience of such support.
PUBLISHED
Keywords: Divorce